Investigations of matrix independent calibration approaches in fast flow glow discharge mass spectrometry. Issue 6 (12th April 2019) - Gonzalez-Gago, Cristina; Šmíd, Petr; Hofmann, Thomas; Venzago, Cornel; Hoffmann, Volker; Gruner, Wolfgang; Pfeifer, Jens; Richter, Silke; Kipphardt, Heinrich
Abstract : The performance of glow discharge mass spectrometry (GD-MS) is investigated for the accurate quantification of metallic impurities and oxygen in solid samples using the fast flow source GD-MS instrument ELEMENT GD. Abstract : The performance of glow discharge mass spectrometry (GD-MS) is investigated for the accurate quantification of metallic impurities and oxygen in solid samples using the fast flow source GD-MS instrument ELEMENT GD. Different quantification approaches based on relative and absolute sensitivity factors are evaluated for the determination of metallic impurities using three sample matrixes (Al, Cu and Zn). The effect of the discharge conditions (voltage, current, discharge gas pressure/flow) on the sensitivity is investigated and the parameters are optimized to favour matrix independent calibrations. Improved standard relative sensitivity factors (StdRSFs) are calculated under optimal conditions based on multi-matrix calibrations. The sputtering rate corrected calibration is also presented as a multi-matrix calibration approach. The capabilities of GD-MS for oxygen determination are also investigated using a set of new conductive samples containing oxygen with mass fractions in the percent range in three different matrices (Al, Mg and Cu) produced by a sintering process. Poor limits of detection (in the order of g kg −1 ) were obtained as consequence of the reduced sensitivity of oxygen in GD-MS and high oxygen background signal intensity as well as its variations. The absolute sensitivity procedure is shown as a matrix-independent approach, which provides quantitative values consistent with those obtained by carrier gas hot extraction (CGHE).